AB0009 Gender-associated differences of dectin-2, dc-sign and mcp-1 polymorphisms in the susceptibility to rheumatoid arthritis. (23rd January 2014) - Canet, L. M.; Cáliz, R.; Lupiañez, C.; Escudero, A.; Filipescu, I.; Romani, L.; Segura-Catena, J.; Soto-Pino, M. J.; Expósito-Ruiz, M.; Ferrer, M. A.; García, A.; González-Utrilla, A.; et al.
Abstract : Background: Hormonal, environmental and genetic factors interact in the development of rheumatoid arthritis (RA) but it is still not clear which factors are responsible for the observed gender associated differences in RA incidence and severity. Given that the invasion of RA synovial by macrophages (and subsequently by T-cells) is a critical step that requires the involvement of several immune molecules and given the role of genetic variants in determining the immune response, the present study was conducted to explore whether single nucleotide polymorphisms in immune-related genes might differentially influence the risk of RA in women and men. Methods: Twenty-seven functional/tagging polymorphisms in Dectin-1, Dectin-2, DC-SIGN, MCP-1 and CCR2 genes were selected and genotyped in 970 individuals, 458 RA patients (359 women and 99 men) and 512 healthy controls (217 women and 295 men). Results: We found that women carrying the Dectin-2 rs4264222_T and Dectin-2 rs7134303_G alleles had an increased risk of RA (OR=1.95, 95%CI 1.35-2.82 and OR=1.91, 95%CI 1.29-2.83) whereas women carrying the MCP-1 rs1024611_G, and MCP-1 rs13900_C alleles had a decreased risk of RA compared with those carrying the wild-type genotype (OR=0.60, 95%CI 0.42-0.86 and OR=0.65, 95%CI 0.46-0.93). In men, none of these associations were observed but we found that carriers of the DC-SIGN rs2287886_A allele had an increased risk of RA (OR=1.69, 95%CI 1.03-2.78) whereas carriers of the DC-SIGN rs4804803_G had a decreased risk of developing the disease (OR=0.54, 95%CI 0.32-0.91). SNP-SNP interaction analysis showed significant three- and four-locus interaction models in women that were not seen in men. Across all these models, the most accurate predictor was a model that consisted of DC-SIGN rs4804803, Dectin-2 rs4264222 and Dectin-2 rs7134303 polymorphisms and suggested a synergistic effect between Dectin-2 rs7134303 and Dectin-2 rs4264222. Conclusions: These results suggest that Dectin-2, MCP-1 and DC-SIGN polymorphisms may account for gender-associated differences in susceptibility to RA. Future studies in larger populations are needed to corroborate our findings. Disclosure of Interest: None Declared